Towards integrated financing for a climate-neutral European Union: brak - Szafran, Joanna (Ekonomia i Prawo. Economics and Law, 2025)
Abstract Motivation: The biggest challenge for achieving the Paris commitments and the European Union’s 2030 and 2050 climate and energy targets in a just transition is to provide long-term support through coherent policies and instruments that increase public and private funds for climate transition. Due to the complexity of the ’super wicked’ climate change problem, scientists and some politicians (European Commission) recommend mainstreaming or ’integration’ of climate objectives into non-climate policy areas. The study answers whether these declarations are followed by the integration of financing in EU policy and fills the gap in the literature on integrating climate policy instruments. Aim: This paper examines the progress in integrating the sources and mechanisms of financing the European Union’s transition towards net-zero emissions. Results: Climate policy integration is an ongoing process that requires adjustments to activities and sources of financing. The Multi-Annual Budget and the Recovery Resilient Facility, the support of the EIB Group, national development banks and other financing institutions provide the financial, technological and political conditions for achieving the 2030 and 2050 targets. The revenues from market mechanisms (EU ETS) feed into specialised funds and public programmes, and repayable funding instruments (e.g. InvestEU Fund, the EIB) complement non-repayable funding (Structural and Investment Funds). New instruments such as the Just Transition Mechanism, the Modernisation Fund and the Social Climate Fund aim to increase public support by mitigating the costs of the transformation.